Karakterisasi Sifat Fisikokimia Komposit Besi Oksida-Montmorilonit Hasil Interkalasi Silikat Lempung Montmorilonit - Serly Jolanda Sekewael (Hasanuddin University, 2008)
The preparation of iron oxide-montmorillonite composite has been done by intercalation of iron oxide into the silicates interlayer of montmorillonite. Montmorillonite and iron oxide-montmorillonite composite were characterized to observe some physical and chemical properties. The observed properties were basal spacing d001, determined by X-Rays Difractometer (XRD); surface morphology, analyzed by SEM/EDAX; specific surface area, distribution of pore radius and total pore volume, analyzed by Gas Sorption Analyzer; functional groups, analyzed by FTIR Spectrophotometer; and iron content, determined by X-Ray Fluorescent Analyzer (XRF). The characterization of montmorillonite and iron oxide-montmorillonite composite showed that the basal spacing d001, increased from 14.11 Å in montmorillonite to 16.85 Å in iron oxide-montmorillonite. Surface morphology of montmorillonite showed the laminated structure, while that of iron oxide-montmorillonite indicated a delaminated structure with the external oxides layered. Specific surface area increased from 69.71 m2/g to 126. 49 m2/g; total pore volume also increased from 50.70 x10-3 mL/g to 107.89 x10-3 mL/g. Generally, spectrum adsorption of montmorillonite and iron oxide-montmorillonite composite not different so far, stretching vibration O-H with Fe3+ does not exist on iron oxide-montmorillonite composite. The iron content also increased from 4.57 %(w/w) to 23.61 %(w/w).Keywords : montmorillonite clay, intercalation, iron oxide-montmorillonit composite.